1976
DOI: 10.1063/1.323079
|View full text |Cite
|
Sign up to set email alerts
|

Variational analysis of the reflection of surface waves by arrays of reflecting strips

Abstract: A system of approximate surface wave equations and edge conditions in one scalar variable is derived from Hamilton’s principle for linear piezoelectric media by assuming suitable depth behavior and integrating with respect to depth. The assumed behavior with depth is determined from the known surface-wave solutions of the three-dimensional equations for both the plated and unplated substrate. The influence of the inertia, stiffness, and electrical shorting of the film is included in the analysis. The approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] One of the fundamental characteristics allowing to estimate the influence of the surface state on the SAW propagation is the reflection coefficient from single obstacles, such as steps or grooves. Various theoretical methods have been put forward to derive this coefficient: perturbation techniques, 4-7 variational method, 8 impedance method, 9,10 and integral equation method. 11 It has been found that the absolute values of the first-order reflection coefficients from grooves and from projections of the same shape as grooves are identical but their phases differ by .…”
Section: Rayleigh Wave Reflection From Single Surface Imperfections Omentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] One of the fundamental characteristics allowing to estimate the influence of the surface state on the SAW propagation is the reflection coefficient from single obstacles, such as steps or grooves. Various theoretical methods have been put forward to derive this coefficient: perturbation techniques, 4-7 variational method, 8 impedance method, 9,10 and integral equation method. 11 It has been found that the absolute values of the first-order reflection coefficients from grooves and from projections of the same shape as grooves are identical but their phases differ by .…”
Section: Rayleigh Wave Reflection From Single Surface Imperfections Omentioning
confidence: 99%
“…Numerous analyses of such interactions have appeared [1][2][3][4][5][6][7]. A common feature among all of these is the representation of the surface layer by a set of boundary conditions [8] to be applied to fields in the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The Wiener-Hopf technique is useful in some very special cases with semi-infinite layers [1-3] but even here usually leads to integrals which can be evaluated only numerically. A variational approach [4][5] and various related modal expansion techniques [6] are more widely applicable and have proven successful for many applications, but have not given any insight into the radiated wave, as they incorporate an assumed field consisting only of surface waves. A direct, approximate, numerical solution has been obtained for a single strip [7], but the numerical analysis is exceedingly complex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations